(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Services in the cloud environment are distributed between all servers and users. Cloud providers have problems with file protection as security is a major problem when processing and transferring information, as the original data type can be viewed, misused and lost. In the cloud computing world, cloud protection is a major concern. A variety of research projects are planned to safeguard the cloud climate. Cryptography is used to address the security problem and to achieve the CIA (confidentiality, honesty and disponibility). The most effective technique for ensuring high data transfer and storage protection is cryptography. There are certain drawbacks in traditional symmetric and asymmetrics. We will introduce a new technique of hybrid data protection and confidentiality to solve this issue. We use the ECC and Blowfish to build a hybrid algorithm in this article. The hybrid scheme output is compared to the current hybrid technique and demonstrates the high safety and confidentiality of the patient data in the proposed method. The hybrid encryption is used to remove both symmetrical and asymmetrical drawbacks.